Targeting pancreatic cancer with natural compounds: molecular mechanisms, preclinical evidence, clinical perspectives, and limitations - Alberto Orta; Miguel Angel Hidalgo-Leon; Carlos Lacalle-Gonzalez; Miriam M. Rodriguez de Lope; Lara Sanz-Criado; Jesus Garcia-Foncillas; Javier Martinez-Useros (Frontiers in Pharmacology, 2026)
Pancreatic cancer remains one of the most aggressive and lethal malignancies, with poor survival outcomes and limited therapeutic options. Surgical resection is currently the only potentially curative treatment; however, fewer than 20% of patients are eligible for this at diagnosis due to the stage of the advanced disease. Despite substantial progress in understanding the molecular pathogenesis of pancreatic cancer, effective targeted therapies remain scarce, and current systemic treatments provide only modest clinical benefit. In this context, natural compounds have attracted growing interest as potential anti-cancer agents because of their antioxidant, anti-inflammatory, and multi-target biological activities. Increasing preclinical evidence has demonstrated significant anti-tumor effects in pancreatic cancer models, including the inhibition of proliferation, induction of apoptosis, modulation of metastatic behavior, and enhancement of chemosensitivity. However, their clinical translation is still limited by poor bioavailability, pharmacokinetic variability, and incompletely characterized pleiotropic mechanisms of action. This review provides a comprehensive and critical overview of the current evidence regarding selected natural compounds in pancreatic cancer, including apigenin, cannabinoids, curcumin, luteolin, quercetin, resveratrol, vitamin C, and vitamin D. We summarize their molecular targets, therapeutic potential, and translational limitations, with the aim of supporting the design of future clinical studies and facilitating their integration into precision oncology strategies.